Can any one help with two problems I have
x/xy+x^2 + y/x^2+xy =x/y(x+y) +y/x(x+y)=x^2/xy(x+y)+y^2/xy(x+y)=x^2+y^2/xy(x+y)
with this ome I can work out why xy(x+y) s the common factor and why the x and th Y become squared.
1/x^2+x - 1/x+1 = 1/x(x+1) -x/x(x+1)
with this one why does the x appear as a numerator
hope this all makes sence.
The "1/x(x+1) - x/x(x+1)" in previous post needs further bracketing:
1 / [x(x+1)] - x / [x(x+1)]
Your starting expression should be shown this way:
1 / (x^2 + x) - 1 / (x + 1) ; then:
= 1 / [x(x + 1)] - 1 / (x + 1)
= 1 / [x(x+1)] - x / [x(x+1)]
= (1 - x) / [x(x + 1)]
lose our time trying to decipher what you mean. Your original expression "x/xy+x^2 + y/x^2+xy"
MUST be shown this way:
x / (xy + x^2) + y / (x^2+xy) ; and
x / (xy + x^2) = x / [x(x + y)] , not x / [y(x + y)] as you have...
For your benefit:
20 / (2 + 3) = 20 / 5 = 4
20 / 2 + 3 = 10 + 3 = 13
See the importance of proper bracketing?